Hedychium coronarium Rhizomes: Promising Antidiabetic and Natural Inhibitor of α-Amylase and α-Glucosidase. (2nd January 2020) - Panigrahy, Suchitra K.; Kumar, Awanish; Bhatt, Renu
Abstract: Hedychium coronarium Koen., commonly known as ginger lily, is considered an endemic medicinal plant. In the present study, the antidiabetic action of its rhizomes was investigated by α-amylase and α-glucosidase inhibition assay, and the active compounds were identified through bioactivity guided isolation technique. Among the six different extracts, the EA extract has shown highest inhibition, and the subfractions from active EA extract were separated by silica gel column chromatography. The subfraction showing highest inhibition was investigated for its chemical composition by high-resolution liquid chromatography–mass spectroscopy (HRLC-MS/MS). The fatty acids such as suberic acid and terpenes such as triparanol, ginkgolide C, and swietenine were found to be the major compounds in the subfractions. The present work revealed that H. coronarium rhizome extract and its active constituent could be used as a natural inhibitor of these two carbohydrate-metabolizing enzymes and may play a key role in the management of diabetes.